Asymmetric Formal Synthesis of Azadirachtin. (16th October 2015) - Mori, Naoki; Kitahara, Takeshi; Mori, Kenji; Watanabe, Hidenori
Abstract: An asymmetric formal synthesis of azadirachtin, a potent insect antifeedant, was accomplished in 30 steps to Ley's synthetic intermediate (longest linear sequence). The synthesis features: 1) rapid access to the optically active right‐hand segment starting from the known 5‐hydroxymethyl‐2‐cyclopentenone scaffold; 2) construction of the B and E rings by a key intramolecular tandem radical cyclization; 3) formation of the hemiacetal moiety in the C ring through the α‐oxidation of the six‐membered lactone followed by methanolysis. Abstract : Die formale asymmetrische Synthese von Azadirachtin (1 ) gelang über eine Tandem‐Radikalcyclisierung als Schlüsselschritt. Die längste lineare Sequenz zu der entscheidenden Zwischenstufe 2 umfasst 30 Stufen.